Perancangan Media Pembelajaran untuk Menunjang Kegiatan Belajar Siswa Berbasis Android - Dewi Diyani; Juliana Juliana; Siti Khotijah (Universitas Indraprasta PGRI Jakarta, 2018)
The increasingly rapid development of information technology, especially in communication tool, has created smartphones with Android operating system. The android can provide attractive features to users consisting of not only adults, but also children. Children can spend hours, or even all day long to use Android. A lot of time spent by them to use Android, causes dependence on Android, hampering children's development. Considering the problems, the researcher then designs a learning medium by utilizing the development of Android technology with the aim of helping school-aged children, especially students at the TKQ or TPQ level with learning activities by utilizing the android development. The research uses waterfall method, in which the data are analyzed in several stages, namely designing, coding, testing and implementing, The program used to design the application is Appy Pie. The tools used to design the learning medium include Unified Modeling Langunge (UML) and flowcharts. The result of this study is an application that contains Islamic learning explaining information on worship such as prayer, Al-Qur’an recital as well as an educational game discussing Islamic learning.